Recent deforestation drove the spike in Amazonian fires - Cardil, Adrián (2020)
Tropical forests are of global importance even though they only cover around 10% of the Earth's land surface. They store large amounts of carbon and host between one-half and two-thirds of the world's species (Lewis 2006). Small changes in the tropical moist forest—the most biodiverse biome within the tropical forests—may lead to global impacts on climate dynamics and warming, water cycles, and the loss of biodiversity. If the current rates of deforestation and clearing patterns continue, many tropical moist forests could face an imminent regime shift towards an alternative tropical scrubland ecosystem state (Lovejoy and Nobre 2018). Over the last several months of 2019, there was a surge of headline news by global media of widespread wildfires in the Amazon rainforest, the largest remaining expanse of tropical moist forest on Earth. Smoke from Amazon fires, visible from space, engulfed cities thousands of kilometers away, including São Paulo, the largest South American city, which plunged into darkness at 3 pm on 19 August 2019. The long-term socioeconomic and environmental impacts of such fires could potentially be severe, not only in regards to the amount of particulate matter released into the atmosphere, but also contributing toward massive carbon dioxide emissions from fires. These will threaten biodiversity in one of the most megadiverse regions of the world, causing negative impacts on human health, and immense economic damage (de Mendonça et al 2004, Aragão et al 2018, Smith 2019, Brancalion et al 2020). Given these social and ecological losses, the ultimate reason behind the widespread fires in the Amazonian rainforest has become a focus of public inquiries. In the vacuum created by a lack of scientific assessments, contrasting narratives and polarized opinions have proliferated. Considering the fact that the doubling of fire incidence in August―the peak fire month in 2019―relative to the average August fire incidence over the last decade was not influenced by severe droughts or other climatic anomalies (Barlow et al 2020, Kelley et al 2020), what caused the 2019 Amazon fires anomaly?